Comment on the paper "On the formation of hierarchical microstructure in a Mo-doped NiCoCr medium-entropy alloy with enhanced strength-ductility synergy" by J. He, S.Makineni, W.Lu, Y.Shang, Z.Lu, Z.Li, B.Gault, Scripta Mater 175(2020)1-6. (October 2020) - Hausch, G.
Abstract: It is shown that the composition of the investigated alloy is nearly identical to the commercially available alloy MP35N (35Co-35Ni-20Cr-10Mo, wt%). However, the thermomechanical treatment of the experimental alloy is quite different from that used for the commercial one which consists of using cold work followed by annealing at temperatures below the recrystallization temperature. Here, depending on the amouunt of cold work, a tremendous hardening effect occurs, due to Suzuki hardening which allows to tune the mechanical properties in a range much larger than obtainable by the strategy used by the High Entropy Community by creating hierarchical microstructures.